TEACHING AND EDUCATION - Maya Mainkar (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: There is poverty extreme poverty, in the world, despite increased literacy rates. This means education has fallen short of its promise, because it has left a very large number of human beings deprived of basic needs of existence. In addition, bizarre diseases, related to the aberrations of the mind, have increased considerably over the years, despite the growth of research in medicine. Why is there dissatisfaction with education despite increase in literacy rates and such elaborate discussions throughout the world on how to make learning interesting and effective? The answer to this is obvious. We link education to passing examinations and going to the next class but not to excellence of existence. Teachers rarely realize that knowledge is not power. Thinking does not come automatically to human beings. They can at best manage arbitrary or elementary thinking. Creative and purposeful thinking has to be taught in schools much more than providing random information Key words: education, teaching, literacy